Zak transform and uncertainty principles associated with the linear canonical transform. Issue 7 (1st September 2016) - Zhang, Qingyue
Abstract : Several new results about Zak transform and uncertainty principles in the linear canonical transform (LCT) domains are presented. The results obtained rely mainly on relationship between the LCT and the classical Fourier transform. The findings will likely have potential applications in optics and signal processing.